2016
DOI: 10.1038/srep32654
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetics Based On Dehydroepiandrosterone Scaffold: Synthesis, Antiproliferation Activity, Structure-Activity Relationship, and Mechanisms

Abstract: A series of novel peptidomimetics bearing dehydroepiandrosterone moiety were designed, synthesized, and evaluated for their inhibition activities against cell proliferation. According to the preliminary studies on inhibitory activities, some of the newly prepared compounds indicated significantly inhibition activities against human hepatoma cancer (HepG2), human lung cancer (A549), human melanoma (A875) cell lines compared with the control 5-fluorouracil. Especially, compounds Ii (IC50 < 14 μM) and Ik (IC50 < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…On the basis of IC 50 values, it was found that compounds 45c−e and 45g, which have a fluoro-substituted -m) and 95a−l (IIa-l) at 40 μg/mL. 22 Copyright 2016, The Author(s). 5-FU: 5-Fluorouracil, used as a positive control.…”
Section: Synthesis and Pharmacological Properties Of Dehydroepiandros...mentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of IC 50 values, it was found that compounds 45c−e and 45g, which have a fluoro-substituted -m) and 95a−l (IIa-l) at 40 μg/mL. 22 Copyright 2016, The Author(s). 5-FU: 5-Fluorouracil, used as a positive control.…”
Section: Synthesis and Pharmacological Properties Of Dehydroepiandros...mentioning
confidence: 99%
“…Wang et al (2016) reported a series of novel peptidomimetics bearing DHEA moiety (94a−m and 95a−l) that was designed and synthesized using N-protected amino acids 91a−m and DHEA-17 hydrazone 92/DHEA-17 oxime 93 through nucleophilic substitution (Scheme 13). 22 Besides, the inhibition activity of the newly prepared compounds was evaluated against HepG2 (human hepatoma carcinoma), A549 (human lung), and A875 (human melanoma) cancer cell lines using the standard MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay compared with 5-FU (5-Fluorouracil) as a positive control. The majority of the compounds had higher inhibitory actions than 5-FU, as demonstrated in Figure 8.…”
Section: Pyrazole and Imidazole Dehydroepiandrosteronementioning
confidence: 99%
See 2 more Smart Citations
“…Producing peptidomimetics can be accomplished in several ways, including the following: (i) manipulating native peptide backbones, (ii) coupling unnatural amino acids derived from modifications, (iii) replacing amino groups with oxygen or sulfur by isosteric substitution (Gomes Von Borowski et al 2018 ; Wang et al 2016 ). Structure, sequence, function, and protein binding site characteristics are all factors that influence the design strategy (Lenci and Trabocchi 2020 ).…”
Section: Introductionmentioning
confidence: 99%